Illegal Evidence in Criminal Proceedings: Collection of Evidence by Authorized Officials of Internal Affairs Bodies - Živanović, Katarina S. (NBP. Nauka, bezbednosti, policija, 2024)
The subject of the research is illegal evidence, i.e. the way in which authorized officials of the internal affairs authorities act, which may cause the illegality of the obtained evidence during the conducting evidential actions. The goal of the research is reflected in the scientific and practical contribution to the scientific and social community, since, in addition to the presentation and analysis of prominent scientific and theoretical concepts represented in domestic and foreign literature, the work contains a detailed presentation of the results of the analysis of judicial decisions of domestic courts, which gain particular importance having in the view that the institute of illegal evidence de facto represents judicial standards. Namely, the results indicate cases in which the court judged the evidence obtained by the police to be illegal, as well as cases in which, contrary to the claims of the legal remedy applicant, the court judged that the police did not act contrary to the legal norm when collecting evidence. In most cases, the following evidentiary actions are involved, provided for by the Criminal Procedure Code of Republic of Serbia: interrogation of the accused (Art. 85-90), investigation (Art. 133-136), temporary confiscation of items (Art. 147-151) and search (Art. 152 -160). In cases where the court still found that the evidence obtained by the police was illegal, it is not a question of a deliberate and gross violation of basic human rights and freedoms, that is, it is not a question of incriminated behavior of police officers, such as extorting a confession or abuse and torture.